Racism, Violence and the Suffering of Black Women: Dialogs Based on Heleith Saffioti - Gouveia Passos, Rachel (Pontifícia Universidade Católica de São Paulo, 2021)
This article takes as its point of departure the stories and data produced by the following problematics: what are the effects of State violence on the life of black women? What responses have been made available by the public sector for the suffering that was caused? These questions lead us to interrogate the suffering of black women, caused by state violence, based on dialogues with Heleith Saffioti.